Analyzing crop price dynamics in Nalanda, Bihar: An in-depth analysis of twenty agricultural commodities - Mohanty, Samarendu; Bairagi, Subir; Janakiraman, Deepa; Baruah, Sampriti; Kakraliya, Manish; Krupnik, Timothy J. (TAFSSA, 2023)
In this study, we investigated market integration and price transmission dynamics in agricultural supply chains in Nalanda, Bihar, focusing on twenty commodities. We utilized daily price data from Noorsarai and Harnaut village markets, the Bihar Sharif intermediate market, and the Patna City market with the aim of understanding the interrelationships among these prices. Our findings suggest that most crop prices tend to vary concurrently, necessitating adjustments for improved precision and accuracy in price assessments. We also observed notable linkages between smaller village markets and larger markets, influenced by factors such as minimum support prices and transportation costs. Through causality tests, we identified bidirectional influences in certain markets, revealing the complex nature of price transmission dynamics. These insights can contribute to a better understanding of inter-market price relationships, potentially aiding policymakers in refining Bihar’s agricultural supply chains such that they can better support farmgate prices received by smallholder farmers. More generally, this work provides practical insights on how prices can be better aligned between diverse value chain actors, including smallholder farmers, traders, and marketers in India's agricultural markets. This work highlights how price dynamics and market integration that can be studied in a variety of contexts beyond Nalanda, Bihar, and which are important to aid in making informed decisions about crop production, pricing, and market access, particularly for smallholder and marginalized farmers.